cGAS-STING signaling in cardiovascular diseases - Zhang, Qianxin; Shen, Lijuan; Ruan, Hongbiao; Huang, Zhouqing (Frontiers in Immunology, 2024)
Sterile inflammation, characterized by a persistent chronic inflammatory state, significantly contributes to the progression of various diseases such as autoimmune, metabolic, neurodegenerative, and cardiovascular disorders. Recent evidence has increasingly highlighted the intricate connection between inflammatory responses and cardiovascular diseases, underscoring the pivotal role of the Stimulator of Interferon Genes (STING). STING is crucial for the secretion of type I interferon (IFN) and proinflammatory cytokines in response to cytosolic nucleic acids, playing a vital role in the innate immune system. Specifically, research has underscored the STING pathway involvement in unregulated inflammations, where its aberrant activation leads to a surge in inflammatory events, enhanced IFN I responses, and cell death.The primary pathway triggering STING activation is the cyclic GMP-AMP synthase (cGAS) pathway. This review delves into recent findings on STING and the cGAS-STING pathways, focusing on their regulatory mechanisms and impact on cardiovascular diseases. It also discusses the latest advancements in identifying antagonists targeting cGAS and STING, and concludes by assessing the potential of cGAS or STING inhibitors as treatments for cardiovascular diseases.